Association between Group 2 Innate Lymphoid Cells enrichment, nasal polyps and allergy in Chronic Rhinosinusitis. Issue 9 (13th June 2014) - Miljkovic, D.; Bassiouni, A.; Cooksley, C.; Ou, J.; Hauben, E.; Wormald, P. ‐J.; Vreugde, S.
Abstract Background Group 2 innate lymphoid cells (ILC2s) were shown to be involved in the initiation and coordination of Th2‐type immune responses in allergic disease animal models. Recently, ILC2s enrichment was noted in chronic rhinosinusitis (CRS) patients; however, the role of ILC2s in coordinating the Th2 response in CRS remains to be elucidated. Here, we characterize the ILC2 compartment in CRS by investigating the correlations between ILC2s, Th2 cells and Th2 cytokines expression in CRS patients. Methods We used flow cytometric analysis of sinonasal mucosal tissues of 29 CRS patients and 5 controls to quantify ILC2s and Th2 cells. Messenger RNA expression levels of IL‐5, IL‐13, IL‐25, IL‐33, TSLP and GATA3 were determined using qRT‐PCR. Results ILC2s were significantly enriched in nasal polyps (CRSwNP) patients. Multivariate linear regression showed a significant positive association of ILC2 numbers with CRSwNP and allergic CRS and a negative association with the number of previous endoscopic sinus surgeries. Group 2 innate lymphoid cell numbers significantly correlated with Th2 cell frequencies. Messenger RNA expression levels of IL‐5 and IL‐13 were increased in CRSwNP compared with controls, while mRNA levels of IL‐25 and GATA3 were significantly reduced. Conclusions Our results characterize the complex interactions between ILC2s and other Th2 response elements in the context of CRS and suggest that ILC2 enrichment occurs in CRSwNP and in allergic CRS patients.